The Snow White’s Character’s Modification in “Snow White and The Seven Dwarfs by Regis Maine” and “Snow White and The Seven Dwarfs by Vera Southgate” Seen from Feminist Theory - Arimbawa, I Made (Jurnal Penelitian Mahasiswa Indonesia, 2023)
In this article discuss about the character Snow White in Snow White and the Seven Dwarfs by Vera Southgate and Snow White and the Seven Dwarfs by Regis Maine. The Story written by Vera Southgate is one of the stories that had a major influence on women’s behavior. Where is the character Snow White was depicted as beautiful, kind, and has a handsome husband, it was made many women want to be like Snow White. Meanwhile, the Story by Regis Maine is also told the same main character, but there are the differences between the main characters in both of the stories. Character Snow White in Snow White and the Seven Dwarfs by Regis Maine is one of form Feminist movement. Because the character Snow White by Regis Maine or comic version is hard-worker, brave, strong, and active. While, in the story by Vera Southgate she was depicted as lazy, passive, weak and too innocent. So, from that, the female character in Snow White and the Seven Dwarfs by Regis Maine should be one of the good inspirations for the women.